Penerapan Strategi Hembusan Angin Kencang untuk Meningkatkan Motivasi Belajar Siswa Kelas IV pada Mata Pelajaran PAI di SDN 007 Kampung Baru Kecamatan Cerenti Kabupaten Kuantan Singingi - Deswani Deswani; Sopiatun Nahwiyah; Ikrima Mailani (LEMBAGA PENELITIAN DAN PENGABDIAN MASYARAKAT (LPPM) UNIKS, 2019)
Abstract Learning motivation is very important for realizing educational goals, the problem in SD N 007 Kampung Baru Cerenti Subdistrict Kuantan Singingi Regency is that students do not have good learning motivation such as: Students often make noise in the PAI learning process, Students are lazy to learn especially on subjects PAI, Students do not do the assignments given by the teacher, Students are not enthusiastic in the class when they attend PAI learning. Thus the need for a strategy that can increase learning motivation is by using strong wind blowing strategies, with the formulation of how the application of the strategy of gusts of wind to increase the learning motivation of fourth grade students in PAI subjects in SD N 007 Kampung Baru Cerenti Subdistrict Kuantan Singingi Regency. The results of this study were 12.50% Prasiklus, after cycle 1 (the initial implementation of the strategy of gusts of wind) reached 62.50%, cycle 2 increased to 75% and cycle 3 also had a very significant increase which reached 100%. This proves that the application of strong wind blowing strategies can increase the learning motivation of fourth grade students in PAI subjects in SD N 007 Kampung Baru Cerenti Subdistrict, Kuantan Singingi Regency effectively and can increase student learning motivation in PAI subjects. Keywords: Strategy for Blowing Strong Winds, Learning Motivation